(3eONd eJcGeds - (3UGdM QTjO(B, (3YHO GdQVGs; (3LdGH OgT GMSGf(B, s ((3YeGf(B:s (3OGQ GdefGgL(B,s, 2008)
(3JWhQ GdacQ GdGSJQGJjLj, ebOeI aj GdGOGQI GdGSJQGJjLjI, JMdjd GdHjFI GdNGQLjI, GdJMdjd GdJfXjej, GdQDjI GdGSJQGJjLjI hQSGdI GdefXeI, CgOGa GdefXeI, GdNjGQ GdGSJQGJjLj, GSJQGJjLjI GdefXeI, GSJQGJjLjI GdCYeGd, GdGSJQGJjLjI GdhXjajI, GdJfajP GdGSJQGJjLj, GdQbGHI GdGSJQGJjLjI, MGdGJ OQGSjIs
Keywords: (3GOGQI GdGYeGds; (3GdGOGQIs; (3GdGSJQGJjLjIs